Etnografi Garna Tentang Kebudayaan Baduy (Catatan untuk Mengenang Prof H. Judistira K. Garna, Ph.D) - Ade Makmur Kartawinata (Universitas Padjadjaran, 2020)
This article explains the way Judistira K Garna describing Baduy culture. His ethnographic work is about the life of the Baduy people and their response to changes from the perspective of the Baduy themselves. Koentjaraningrat referred Judistira's work as